2018
DOI: 10.1186/s12894-018-0332-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of urolithiasis – a systematic analysis of available guidelines

Abstract: BackgroundSeveral societies around the world issue guidelines incorporating the latest evidence. However, even the most commonly cited guidelines of the European Association of Urology (EAU) and the American Urological Association (AUA) leave the clinician with several treatment options and differ on specific points. We aimed to identify discrepancies and areas of consensus between guidelines to give novel insights into areas where low consensus between the guideline panels exists, and therefore where more evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 24 publications
0
44
0
2
Order By: Relevance
“…Although ESWL has been used as the first option for the treatment of proximal ureteral stones, with the recent developments in ureterorenoscopes leading to the reduction in their diameter and the emergence of flexible devices, URS has become the first treatment choice, in particular for stones >10 mm (6). The technical improvement of lithotripters used predominantly for stone fragmentation has led to an increase in the URS success rates and decrease in the complication rates (7,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ESWL has been used as the first option for the treatment of proximal ureteral stones, with the recent developments in ureterorenoscopes leading to the reduction in their diameter and the emergence of flexible devices, URS has become the first treatment choice, in particular for stones >10 mm (6). The technical improvement of lithotripters used predominantly for stone fragmentation has led to an increase in the URS success rates and decrease in the complication rates (7,12).…”
Section: Discussionmentioning
confidence: 99%
“…If there is no indication for active stone removal, the first treatment option is either conservative monitoring or medical expulsive treatment. According to the European Association of Urology guidelines, if there is an indication for active stone removal (for stones that are not likely to pass spontaneously and in the presence of symptoms, such as persistent pain despite adequate analgesic treatment, persistent obstruction, and renal insufficiency), the first treatment choice for proximal ureteral stones is URS if the stone is larger than 10 mm and ESWL or URS if the stone size is less than 10 mm (6). Studies have shown that the success of URS is affected by the size, location, number and composition of the stone, whether it is impacted, and the lithotripter that is used (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The recommendations on stage III N2 NSCLC within the guidelines were reduced to recommendations towards a definitive surgical approach (with neoadjuvant or adjuvant Ch/CRT), a definitive CRT approach or no preference (no specific recommendation for either RT or surgery and both being options). Decision criteria implemented were analysed and standardised if their meaning was not changed, as described by PANJE et al [25][26][27]. Universal criteria such as the ability to give informed consent were not included in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Stones with a low chance of spontaneous passage, persistent pain despite adequate analgesic treatment, persistent obstruction and renal insufficiency constitute the indications for active ureteral stone removal (5). Currently, treatment options for ureteral stones are observation, medical expulsive therapy, shock wave lithotripsy (SWL), ureteroscopy (URS), percutaneous nephrolithotomy, laparoscopic surgery, and open surgery (6).…”
Section: Introductionmentioning
confidence: 99%